Complete and partial organizing for corporate social responsibility - Rasche, Andreas; de Bakker, Frank G.A.; Moon, Jeremy (Springer, 2013)
This paper investigates different modes of organizing for corporate social responsibility (CSR). Based on insights from organization theory, we theorize two ways to organize for CSR. “Complete” organization for CSR happens within businesses and depends on the availability of certain organizational elements (e.g., membership, hierarchy, rules, monitoring, and sanctioning). By contrast, “partial” organization for CSR happens when organizers do not have direct access to all these organizational elements. We discuss partial organization for CSR by analyzing how standards and cross-sector partnerships make selective use of organizational elements. We maintain that an important feature of the increasing institutionalization of CSR—not only within businesses but also among non-governmental, governmental, and professional actors—is the rise of partial forms of organization. We discuss the contributions to this Special Issue in the context of our theorization of complete/partial organization for CSR and outline avenues for further research.